The Impact of Intellectual Capital and Corporate Governance on Bank Performance in Vietnam - Pham, The Ky; Tran, Phu Ngoc; Vo, Hong Duc (Journal of Finance - Marketing Research, 2023)
Purpose – The importance of corporate governance and intellectual capital on financial performance has largely been ignored in emerging markets. The banking sector is considered to accumulate a higher level of intellectual capital and to adopt a better corporate governance system. We aim to examine the contribution of these two important aspects to the performance of Vietnam’s banking sector. Design/methodology/approach – This paper utilizes data collected from the annual reports of banks in Vietnam from 2011 to 2021. The modified value-added intellectual coefficient (MVAIC) model is adopted to measure a bank’s intellectual capital efficiency. In addition, the generalized method of moments is utilized to ensure the robustness of the findings. Findings – Empirical results strongly confirm that intellectual capital positively contributes to a bank’s performance. In terms of corporate governance, the findings indicate that board size, board remuneration and major shareholders holding more than 20 percent of outstanding shares are the three most important factors that contribute positively to banks’ performance. In addition, human capital efficiency and capital employed efficiency positively impact a bank’s profit. Practical implications – Our study provides valuable evidence and implications for policymakers in managing and enhancing corporate governance and intellectual capital efficiency within the Vietnamese context, particularly in the banking sector. Originality/value – To the best of our knowledge, this is the first empirical paper conducted to examine the contribution of corporate governance and intellectual capital on banks’ performance in Vietnam.